Information literacy, data literacy, privacy literacy, and ChatGPT: Technology literacies align with perspectives on emerging technology adoption within communities - Lund, Brady; Agbaji, Daniel; Teel, Zoë A. (Human Technology, 2023)
This research delves into the interplay between three pivotal literacies in the digital age–information literacy, data literacy, and privacy literacy—and the receptivity towards the adoption of emerging technology within communities, with a specific focus on the chatbot ChatGPT. Data was gathered through online surveys conducted among adults residing in a four-county region in northern Texas during a two-week period in late 2022, yielding 130 valid responses. The results of regression analysis indicate a positive association between the inclination to utilize ChatGPT for enhancing one's community and proficiency in information literacy and privacy literacy. However, an unexpected observation emerges as data literacy skills do not exhibit a significant relationship with this inclination, despite ChatGPT's standing as a data science innovation. Moreover, age, gender, educational attainment, and internet usage patterns are identified as influential factors in these associations. These findings hold substantial importance in comprehending the intricate dynamics of how diverse literacies and individual and community-related variables mutually shape each other's development.